2019
DOI: 10.1016/j.conctc.2019.100419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Music Engagement Program for people with Alzheimer's disease and dementia: Study protocol for a pilot trial

Abstract: Background Alzheimer's disease and dementia are prevalent conditions globally. People with Alzheimer's disease and dementia commonly experience mental health problems, negative emotional states, and behavioural disturbance. Music therapy has previously been used in this population to improve symptoms of mental health problems; however, there is a paucity of evidence-based programs that also explore positive outcomes such as overall quality of life, social outcomes, as well as the acceptability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
5
0
5
Order By: Relevance
“…This meta-narrative review on the previous studies indicated some improvement in the physiological or psychosomatic behaviors of people living with dementia after music intervention [ 30 , 34 , 38 , 51 , 57 , 67 , 70 ]. For example, music intervention may cause decrease in agitation [ 2 , 19 , 21 , 36 , 38 , 39 , 50 ], anxiety [ 19 , 36 , 37 , 43 , 45 , 50 ], depression [ 19 , 37 , 43 , 49 , 50 ], behavioral and psychological symptoms [ 2 , 43 , 44 , 72 ], and boost cognition, memory [ 2 , 14 , 19 , 37 , 41 , 44 , 46 , 48 , 49 ], motor outcome, and quality of life [ 19 , 43 , 44 , 49 ], while there are studies that did not reach any clear conclusion about the effectiveness of music [ 18 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This meta-narrative review on the previous studies indicated some improvement in the physiological or psychosomatic behaviors of people living with dementia after music intervention [ 30 , 34 , 38 , 51 , 57 , 67 , 70 ]. For example, music intervention may cause decrease in agitation [ 2 , 19 , 21 , 36 , 38 , 39 , 50 ], anxiety [ 19 , 36 , 37 , 43 , 45 , 50 ], depression [ 19 , 37 , 43 , 49 , 50 ], behavioral and psychological symptoms [ 2 , 43 , 44 , 72 ], and boost cognition, memory [ 2 , 14 , 19 , 37 , 41 , 44 , 46 , 48 , 49 ], motor outcome, and quality of life [ 19 , 43 , 44 , 49 ], while there are studies that did not reach any clear conclusion about the effectiveness of music [ 18 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Control group: To compare individuals living with dementia who experience music treatment and others who only receive pharmacological treatment or are involved in other activities, it is necessary to divide people with dementia into two groups: a control group or a study group. Although sixteen papers out of 30 [ 18 , 29 , 30 , 34 , 38 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] included both groups in their studies, some studies did not have a control group in their experiments [ 21 , 26 , 28 , 33 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. For example, in two studies [ 54 , 55 ] with both control and study groups, a greater behavioral disturbance was noticed between the study group than the control group.…”
Section: Gaps In the Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Por último, 8 programas se evalúan mediante una metodología mixta (16%). La mayoría de ellos, 6 programas (75%) presentan un método cuantitativo a través de cuestionario con un diseño pretest-postest y como técnica cualitativa la entrevista (Calo et al, 2020;Gulliver et al, 2019;Hirschberg et al, 2020;Low et al, 2020;Riggins & McLennon, 2020;Uhlig et al, 2016).…”
Section: Métodos De Investigación Utilizados Para El Diseño Y Evaluación De Programasunclassified